Changes in synovial fluid biomarkers and clinical efficacy of intra‐articular injections of hyaluronic acid for patients with knee osteoarthritis - Yoshihiro Kusayama; Yasushi Akamatsu; Ken Kumagai; Hideo Kobayashi; Masato Aratake; Tomoyuki Saito (Journal of Experimental Orthopaedics, 2014)
Abstract Background The changes in synovial fluid biomarkers after intra‐articular injection of hyarulonic acid (IA HA) remain controversial. We investigate the changes in the properties of synovial fluid (SF) and clinical symptoms before the first and fifth IA HA. Methods A total of 73 patients (73 knees) with symptomatic knee osteoarthritis were treated with five weekly intra‐articular injections of HA and 55 patients (55 knees) were analyzed. The SF total volume, viscosity, and levels of HA, chondroitin 4‐sulfate (C4S), chondroitin 6‐sulfate (C6S), keratin sulfate, and interleukin (IL)‐6 were measured before the first and fifth injections. Clinical evaluations were performed using the American Knee Society score for physician‐based outcome measurements and Knee injury and Osteoarthritis Outcome Score for patient‐based outcome measurements before the first and fifth injections. Results The SF viscosity and levels of HA were significantly increased, and the total SF volume and levels of chondroitin 4‐sulfate, chondroitin 6‐sulfate, and interleukin‐6 were significantly decreased. The physician‐based and patient‐based outcome scores were improved. Conclusions Our findings speculate that HA injections significantly modulate levels of intra articular biomarkers which may indicate beneficial effect for articular cartilage and synovium membrane.